2023
DOI: 10.1038/s41531-023-00503-2
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem neuromelanin and iron MRI reveals a precise signature for idiopathic and LRRK2 Parkinson’s disease

Abstract: Neuromelanin (NM) loss in substantia nigra pars compacta (SNc) and locus coeruleus (LC) reflects neuronal death in Parkinson’s disease (PD). Since genetically-determined PD shows varied clinical expressivity, we wanted to accurately quantify and locate brainstem NM and iron, to discover whether specific MRI patterns are linked to Leucine-rich repeat kinase 2 G2019S PD (LRRK2-PD) or idiopathic Parkinson’s disease (iPD). A 3D automated MRI atlas-based segmentation pipeline (3D-ABSP) for NM/iron-sensitive MRI ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Additionally, a meta-analysis reported a sensitivity of 82% and specificity of 82% in diagnosing PD at 3T 17 . Few 3T studies have compared PD and ET cohorts with NM imaging, but many with relatively low AUC 36 39 . The best outcomes reported were by Jin et al 40 with an AUC of 0.89, sensitivity of 88%, and specificity of 80% in differentiating PD from ET.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a meta-analysis reported a sensitivity of 82% and specificity of 82% in diagnosing PD at 3T 17 . Few 3T studies have compared PD and ET cohorts with NM imaging, but many with relatively low AUC 36 39 . The best outcomes reported were by Jin et al 40 with an AUC of 0.89, sensitivity of 88%, and specificity of 80% in differentiating PD from ET.…”
Section: Discussionmentioning
confidence: 99%
“…However, experienced raters can achieve excellent reproducibility of manual measurements as our rater 1 achieved intra-rater ICC volume of 0.82 in line with several studies (ICC ranging 0.69-0.95 for manual measurements) [42][43][44][45][46] . Recent NM-MRI studies demonstrated nigral NM damage in LRRK2-associated PD patients 47,48 . Although similar studies validated in several cohorts will help better understand whether nigral neurodegeneration mechanism is similar in genetic and idiopathic PD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while the measured NM-SN was a good discriminator between PD patients and controls, the NM-LC was found to best discriminate among PD subgroups with LRRK2 -PD showing preserved NM-LC content compared to sPD. Based on these observations, the authors speculated that NM-based markers can serve as candidate markers for phenotypic PD features [ 42 ]. In a recent study, we investigated NM-SN differences among sPD, LRRK2 -PD, and GBA1 -PD patients.…”
Section: Imaging Studies Findings In Genetic Forms and Prodromal Phas...mentioning
confidence: 99%